Towards a natural semantics of TWO: HAVE, WITH, and the Ancient Greek nominal DUAL - Postma, Gertjan (Nordlyd, 2026)
The distribution of French inalienable possessive constructions with 1. le/la/les or 2. with son/sa/ses, respectively is to a high degree parallel to Ancient Greek nouns with TWO semantics, that are accompanied by 1. a dual noun or 2. a plural noun, respectively. This parallel stems from a shared syntactic configuration with possessor extraction in the 1-contexts, while a simple binding relation is present in the 2-contexts. Possessor extraction under A-movement is accompanied by the emergence of a WITH/HAVE-context, be it prepositional ‘with’ or by an inflectional INST morphology. This sheds light on the morphological parallel of dual morphology and INST morphology in Proto-Indo-European. The linguistic expression of the arithmetic numbers 2 and 3 in natural language follows a similar instrumental scheme.
Keywords: Ancient Greek; French; dual; instrumental; inalienable possession; possessor extraction